Government Problems and Solution to Improve the Quality and Equity of Education in Indonesia - Rizki Ananda; Sri Mulyani; Helvina Sagita; Habib Muzakki Al Mubarok (Edumaspul: Jurnal Pendidikan, 2023)
Education is essential in the process of humanization in a cultured society. The purpose of the research is to find out the problems and also government solutions to improve the quality and equity of education in Indonesia. It is important to improve the quality of education in Indonesia, because this will help improve the quality of human resources, reduce poverty, improve the quality of life, and improve the progress of the country. This article uses the method of literature study, through source sources such as scientific journals, books and trusted websites, expected to produce relevant information and knowledge. The results showed that to improve the quality and equity of education in Indonesia, the government needs to design a comprehensive and integrated plan so that the problem of quality and equity of education can be overcome with various efforts from the government. Planning is needed to even out education in Indonesia which is fairly still Keywords: Education Quality and Education Equity